A coupled biomass-based nanogenerator with both PENG and TENG and preparation method thereof

By using KNN ceramic nanoparticle filler and regenerated cellulose/PVDF-HFP composite in nanogenerators, the problem of insufficient electrical output performance of pure cellulose films is solved, and a multi-mode electrical output capability with both PENG and TENG is achieved.

CN119401850BActive Publication Date: 2025-04-08XIAN SHUANGWANG ENG CONSULTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510012774.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Existing pure cellulose films can only provide a single piezoelectric output, and the electrical output performance is poor, which cannot meet the needs of multi-mode electrical energy collection.

Method used

KNN ceramic nanoparticle filler was prepared by solid phase method, combined with regenerated cellulose and PVDF-HFP casting precursor solution, and a coupled biomass-based nanogenerator with both PENG and TENG was prepared by casting method.

Benefits of technology

The multi-mode electrical output capability of nanogenerators is realized, the piezoelectric and triboelectric properties are improved, and the stable electrical output performance is ensured at different frequencies and forces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119401850B_ABST
    Figure CN119401850B_ABST
Patent Text Reader

Abstract

The present invention discloses a coupled biomass-based nanogenerator with both PENG and TENG and a preparation method thereof; belonging to the technical field of nanogenerators. By regulating the formation of interchain hydrogen bonds between PVDF-HFP and regenerated cellulose molecular chains, the F chemical bonds with huge electronegativity in regenerated cellulose / PVDF-HFP can provide a good triboelectric effect. At the same time, the added KNN nanoparticle filler can be effectively loaded in the regenerated cellulose matrix and provide good piezoelectric performance. The prepared nanogenerator has excellent piezoelectric and triboelectric output performance. The idea of ​​the present invention is simple and clear. The addition of KNN nanoparticle filler to regenerated cellulose further enhances the electrical output performance. The obtained coupled biomass-based nanogenerator with both PENG and TENG is fully environmentally friendly and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanogenerators, and in particular relates to a coupled biomass-based nanogenerator having both PENG and TENG and a preparation method thereof. Background Art

[0002] Nowadays, with the continuous advancement of scientific research, smart electronic devices with high sensitivity, such as smart phones, electronic skin, flexible sensors and wearable electronic devices, have attracted more and more attention in various fields. At the same time, driven by the rapid development of smart electronic devices, how to provide continuous power for these devices remains an urgent problem to be solved. Traditional power supply equipment has the inherent characteristics of low power density and short life, which cannot fully meet the needs of these electronic devices. Therefore, in recent decades, research on electronic devices with self-powered systems has attracted widespread attention. At the same time, due to the continuous consumption of traditional fossil energy, people urgently need to develop new energy sources. Although new energy sources such as wind energy, hydropower and solar energy have been widely used, these energy collection devices are usually used for large-scale energy collection, and some small mechanical energy in daily life cannot be fully collected and utilized. Therefore, a device called a nanogenerator has been developed, which can effectively collect weak mechanical energy and convert it into electrical energy. This new energy collection method can significantly alleviate the serious problem of traditional energy consumption.

[0003] Among the many types of nanogenerators, piezoelectric nanogenerators (PENG) and triboelectric nanogenerators (TENG) are considered to be the two most promising. They can effectively collect and convert widely distributed but unused mechanical energy, especially micromechanical energy from human movement, such as walking, finger bending, talking and even skin deformation, and convert it into electrical energy for energy collection through piezoelectric effect and triboelectric effect. Nanogenerators are mainly assembled from materials with piezoelectric effect and triboelectric materials, such as piezoelectric ceramics and flexible polymers; piezoelectric ceramics include lead zirconate titanate (PZT) and potassium sodium niobate, and flexible polymers include poly(vinylidene fluoride-co-vinyl chloride-co-vinylidene fluoride) (PVDF-HFP) and polyamide (PA). Although the nanogenerators made of the above traditional materials have excellent electrical output performance, they are environmentally unfriendly, have poor biocompatibility, high prices, and are non-renewable, which also limits their application in some fields. Therefore, the development of biomass energy collection materials with excellent performance, renewability, abundance, and low cost is the focus of current research on nanogenerators. As the most abundant natural polymer on earth, cellulose has attracted widespread attention in recent years due to its green, degradable, and good mechanical properties. Some scientific research results have used natural cotton as a substrate to prepare high-performance piezoelectric films. However, there are still the following key issues to be solved: for example, how to adjust the sintering temperature when preparing KNN ceramics by solid phase method. How to enhance the electrical output performance of films prepared based on pure cellulose. At the same time, due to the influence of its surface roughness and the electronegativity of the material, this cellulose-based film can only be used to collect the electrical output generated by the piezoelectric effect.

[0004] In view of the technical problem that the existing pure cellulose film can only provide a single piezoelectric output and has poor electrical output performance, it is urgent to explore and design a new nanogenerator to further enhance its electrical output performance and make it a multi-mode nanogenerator. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a coupled biomass-based nanogenerator and a preparation method that combines PENG and TENG, so as to solve the technical problem that the existing pure cellulose film can only provide a single electrical output and has poor electrical output performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention discloses a method for preparing a coupled biomass-based nanogenerator having both PENG and TENG, comprising the following steps:

[0008] 1) Mixing a PVDF-HFP casting precursor solution with a regenerated cellulose solution, stirring the solution with ultrasonic for multiple times, and then stirring the solution to obtain a regenerated cellulose / PVDF-HFP binary mixed casting precursor solution; then adding KNN ceramic nanoparticle filler, ultrasonicating the solution again, and heating and stirring the solution to obtain a regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution; casting the regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution, drying the solution once, soaking the solution in a water bath, rinsing the solution, and drying the solution twice to obtain a regenerated cellulose / PVDF-HFP / KNN composite film;

[0009] 2) Cut the regenerated cellulose / PVDF-HFP / KNN composite film obtained in step 1) and stick it between two copper electrodes, and spirally wind the conductive copper wire and stick it on the two copper electrodes to obtain a coupled biomass-based nanogenerator with both PENG and TENG.

[0010] Preferably, in step 1), the mass ratio of the PVDF-HFP casting precursor solution to the regenerated cellulose solution is 1: (0.1-20);

[0011] The stirring reaction time is 10~12h;

[0012] The mass ratio of the regenerated cellulose / PVDF-HFP binary mixed casting precursor solution to the KNN ceramic nanoparticle filler was 100:1;

[0013] The heating and stirring temperature is 50~70℃ and the time is 25~35min.

[0014] Preferably, in step 1), the casting conditions are as follows: injecting the regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution onto the guide plate of an adjustable scraper, adjusting the scraper height to 5-22 μm, and casting at a speed of 10-50 cm / min;

[0015] The primary drying temperature is 25~30℃ and the time is 20~30h;

[0016] The conditions for water bath immersion are: immersion in a water bath at 0-40°C for 30-60 min;

[0017] The flushing conditions are: keep flushing in running tap water for 12 to 15 hours;

[0018] The secondary drying condition is 15~80℃ for 8~12h;

[0019] The thickness of the regenerated cellulose / PVDF-HFP / KNN composite film is 15~20μm.

[0020] Preferably, in step 1), the method for preparing the PVDF-HFP casting precursor solution comprises: adding PVDF-HFP powder and LiCl into a DMAC solution, stirring and reacting, to obtain the PVDF-HFP casting precursor solution.

[0021] Further preferably, the mass ratio of PVDF-HFP powder, LiCl and DMAC solution is (2-5):1:(7-15); the stirring reaction temperature is 30-50°C and the time is 1-2h.

[0022] Preferably, in step 1), the method for preparing the regenerated cellulose solution comprises: soaking the crushed cotton linters in a DMAC solution, heating and stirring the solution once, drying to obtain cotton linters cellulose, adding a DMAC / LiCl mixed solution, heating and stirring the solution twice, standing and centrifuging to obtain a regenerated cellulose solution.

[0023] Further preferably, the mass ratio of cotton linters to DMAC solution is 1:(20-100);

[0024] The temperature of the first heating and stirring reaction is 140~200℃, and the time is 10~50min;

[0025] After drying, cotton linter cellulose is obtained, wherein the drying temperature is 50-100°C;

[0026] The mass ratio of cotton linter cellulose to DMAC / LiCl mixed solution is (2~4):(50~60);

[0027] The DMAC / LiCl mixed solution is prepared by mixing the DMAC solution and LiCl in a mass ratio of 1:(9-12);

[0028] The conditions for the secondary heating and stirring reaction are: first stirring at 80-120°C for 2-5 hours, then stirring at room temperature for 20-30 hours; the standing time is not less than 48 hours.

[0029] Preferably, in step 1), the method for preparing KNN ceramic nanoparticle filler comprises: 2 O 5 、Na 2 CO 3 , K 2 CO 3The ball stone and alcohol are fully mixed, ball milled, dried, ground, sieved, calcined, and ground again to obtain KNN ceramic nanoparticle filler; Nb 2 O 5 、Na 2 CO 3 and K 2 CO 3 The molar ratio of Nb is 5:2:3; 2 O 5、 Na 2 CO 3 and K 2 CO 3 The sum of the masses of the three: the mass ratio of spherical stone: alcohol is 1:2:3.

[0030] More preferably, the calcination temperature is 850-950° C., the heating rate is 3° C. / min, and the holding time is 4 h.

[0031] In a second aspect, the present invention further discloses a coupled biomass-based nanogenerator having both PENG and TENG, which is prepared by the preparation method of the coupled biomass-based nanogenerator having both PENG and TENG.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention discloses a method for preparing a coupled biomass-based nanogenerator having both PENG and TENG. Potassium sodium niobate (K 0.6 Na 0.4 )NbO 3, KNN) ceramic nanoparticle filler is used to prepare the regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution, and a coupled biomass-based nanogenerator with both PENG and TENG is prepared by casting. The idea of ​​the present invention is simple and clear. The added KNN ceramic nanoparticle filler with high piezoelectric performance can enhance the piezoelectric performance of the nanogenerator. At the same time, the PVDF-HFP casting precursor solution added to the regenerated cellulose solution not only has certain piezoelectric performance, but can also synergize with the regenerated cellulose solution and the KNN ceramic nanoparticle filler to enhance the piezoelectric output. At the same time, due to the widely distributed -OH groups in the regenerated cellulose molecules and their unique porous network structure, PVDF-HFP is easy to chemically modify the regenerated cellulose, thereby providing a certain triboelectric output capacity. The regenerated cellulose, PVDF-HFP and KNN ceramic particles are evenly mixed to cast a composite film, which is then dried in a closed oven to form a film. The cross section of the obtained regenerated cellulose / PVDF-HFP / KNN composite film is neat and defect-free, and the surface is neat and wrinkle-free. The addition of KNN ceramic nanoparticle filler can provide excellent piezoelectric properties for the regenerated cellulose / PVDF-HFP / KNN composite film. At the same time, the added PVDF-HFP and the hydrogen bonds in the regenerated cellulose molecular chain are chemically bonded, and -F replaces part of the -OH group. Since the -F chemical bond of the PVDF-HFP molecule in the interchain hydrogen bond has a huge electronegativity, based on the effects of electrostatic induction and triboelectric effect, the electrons cyclically contact and separate between the exciter and the regenerated cellulose / PVDF-HFP / KNN composite film, two materials with different electronegativity, to form a single-electrode mode triboelectric nanogenerator. At the same time, the PVDF-HFP loaded in the regenerated cellulose can effectively form a surface nano-rough structure. This rough nanostructure can expand the effective friction area, thereby improving the output performance of triboelectricity. This method for preparing regenerated cellulose / PVDF-HFP / KNN composite film solves the shortcomings of the existing pure cellulose film that can only provide a single piezoelectric output and has poor piezoelectric output performance. Moreover, the coupled biomass-based nanogenerator combining PENG and TENG prepared in this way does not show obvious performance degradation at various operating frequencies such as 3Hz, 4Hz and 5Hz, proving its wide application scenarios.

[0034] The invention discloses a coupled biomass-based nanogenerator with both PENG and TENG prepared by the above-mentioned method for preparing a coupled biomass-based nanogenerator with both PENG and TENG. This nanogenerator is small in size, low in cost, and has high electrical output performance, with an open circuit voltage of about 20V and a short circuit current of about 0.6μA. While improving the piezoelectric properties of pure cellulose-based materials, the addition of PVDF-HFP increases the ability of the regenerated cellulose / KNN composite film to output electricity through the triboelectric effect on the basis of the previous ability to output electricity only through the piezoelectric effect, thereby enhancing the total electrical output capacity of the coupled biomass-based nanogenerator with both PENG and TENG. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The composition and morphology test diagrams of various materials prepared in Example 1 of the present invention; wherein, (a) is the XRD diagram of KNN ceramic nanoparticle filler; (b) is the XRD diagram of regenerated cellulose / PVDF-HFP / KNN composite film; (c) is the SEM diagram of regenerated cellulose / KNN composite film; (d) is the SEM diagram of regenerated cellulose / PVDF-HFP / KNN composite film;

[0036] Figure 2 The total current output and the decomposition diagram of the PENG and TENG current output waveforms of the coupled biomass-based nanogenerator with both PENG and TENG prepared in Example 1 of the present invention at different frequencies and different forces; wherein, (a1) is the total current output waveform measured at different frequencies; (a2) is an enlarged view of the total current output waveform measured at different frequencies; (a3) ​​is a decomposition diagram of the PENG part waveform of the total current output at different frequencies; (a4) is a decomposition diagram of the TENG part waveform of the total current output at different frequencies; (b1) is a total current output waveform measured at different forces; (b2) is an enlarged view of the total current output waveform measured at different forces; (b3) is a decomposition diagram of the PENG part waveform of the total current output under different forces; (b4) is a decomposition diagram of the TENG part waveform of the total current output under different forces;

[0037] Figure 3 These are the electrical performance test diagrams of the coupled biomass-based nanogenerator with both PENG and TENG prepared in Example 1 of the present invention; wherein, (a) is a long-term current output display diagram; (b) is a long-term voltage output display diagram; and (c) is a test result diagram of lighting an LED lamp. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0039] It should be noted that the terms "first", "second", etc. of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product, or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products, or devices.

[0040] The present invention regulates PVDF-HFP to replace part of the hydrogen bonds in the regenerated cellulose molecular chain so that the -F chemical bonds with huge electronegativity in the regenerated cellulose / PVDF-HFP can provide a good triboelectric effect. At the same time, the added KNN ceramic nanoparticle filler can be effectively loaded in the regenerated cellulose matrix and provide good piezoelectric performance. The prepared nanogenerator has excellent piezoelectric and triboelectric properties. The idea of ​​the present invention is simple and clear. The prepared product further enhances the electrical output performance and has sufficient environmental friendliness due to the addition of KNN ceramic nanoparticle filler in the regenerated cellulose film. It has broad application prospects.

[0041] The present invention discloses a method for preparing a coupled biomass-based nanogenerator having both PENG and TENG, comprising the following steps:

[0042] Step 1: Preparation of KNN ceramic nanoparticle fillers by solid phase method

[0043] 1) First, follow Nb 2 O 5 、Na 2 CO 3 and K 2 CO 3 The molar ratio is 5:2:3, and 13.5819g Nb 2 O 5 , 2.1598g Na 2 CO 3and 4.2583 g K 2 CO 3 Add to the ball mill, add 40.0g of ball stone and 60.0g of alcohol to the ball mill, mix them thoroughly, then place the ball mill on a ball mill and mill for 12 hours, then put the mixture obtained after ball milling into an oven to dry to allow the alcohol to evaporate completely.

[0044] 2) First, the mixture obtained in step 1) was put into a grinding mortar and ground. 2 O 5 、Na 2 CO 3 and K 2 CO 3 The mixed powder is crushed and separated from the ball mill with a sieve. The mixed powder obtained after separation is poured into a crucible, and the crucible is covered with a lid and placed in a muffle furnace for firing. The temperature of the muffle furnace is set to 850~950℃, the heating rate is 3℃ / min, and the insulation time is 4h. After that, the fired powder is taken out and poured into a grinding body for grinding for 30min to make the powder fully dispersed, and finally KNN ceramic nanoparticle filler is obtained.

[0045] Step 2: Preparation of regenerated cellulose solution

[0046] 3) Use a blender to break up 2-4 g of cotton linters and put them into a flask. At the same time, add 220 g of N,N-dimethylacetamide (DMAC) solution into the flask and soak the cotton linters in the DMAC solution for more than 48 hours. The mass ratio of cotton linters to DMAC solution is 1:(20-100). After soaking, move the flask to an oil bath-magnetic stirrer and stir at 140-200°C for 10-50 minutes to activate cellulose and enhance the bending vibration and stretching vibration of the groups on the cellulose macromolecular chain. When the temperature in the flask drops to 80-90°C, take out the cotton linters, move the soaked cotton linters into a culture dish to squeeze out a large amount of DMAC solution, and then transfer to a vacuum environment at 50-100°C for drying, remove the remaining DMAC solution, and obtain cotton linters cellulose.

[0047] 4) adding 2-4 g of the cotton linter cellulose obtained in step 3) to 50-60 g of a DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution is 1:(9-12); stirring at 80-120° C. for 2-5 h, and then stirring at room temperature for 20-30 h to obtain a regenerated cellulose casting precursor solution; then leaving the flask to stand to precipitate impurities in the regenerated cellulose solution.

[0048] 5) Pour the regenerated cellulose solution that has been standing for no less than 48 hours into a centrifuge tube and centrifuge it at a centrifugal speed of 5000r / min for 15 minutes to fully separate the impurities from the regenerated cellulose solution. After the centrifugation, pour the clear and transparent regenerated cellulose solution without impurities in the centrifuge tube into a clean container and seal it for storage.

[0049] Step 3: Preparation of PVDF-HFP casting precursor solution

[0050] 6) Add 2-5 g PVDF-HFP powder to the DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution is 1:(7-15); and stir at 30-50°C for 1-2 hours to obtain a PVDF-HFP casting precursor solution;

[0051] Step 4: Preparation of regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution

[0052] 7) The PVDF-HFP casting precursor solution obtained in step 6) and the regenerated cellulose solution obtained in step 5) are mixed in a mass ratio of 1:(1-20), ultrasonically treated for 1-3 hours, and then heated and stirred at 50-100°C for 1-3 hours. During the ultrasonic stirring process, PVDF-HFP chemically modifies the intrachain hydrogen bonds of cellulose, wherein the -F chemical bonds with stronger electronegativity replace part of the hydrogen bonds, thereby enhancing the electronegativity of cellulose, thereby forming a single-electrode mode triboelectric nanogenerator between friction materials with different electronegativity, and forming a nano-rough structure in cellulose that is beneficial to enhancing the triboelectric output capacity. After the chemical modification is completed, a regenerated cellulose / PVDF-HFP binary mixed casting precursor solution can be obtained; then add 1wt.% of KNN ceramic nanoparticle filler accounting for the total mass, mix and ultrasonicate for 30 minutes, then stir at room temperature for 30 minutes, repeat this cycle 5 to 10 times, finally transfer to a magnetic stirrer and continue stirring for 10 to 12 hours, then ultrasonicate at room temperature for 1 hour, heat and stir at 50 to 70°C for 25 to 35 minutes, and obtain a regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution.

[0053] Step 5: Preparation of regenerated cellulose / PVDF-HFP / KNN composite film

[0054] 8) The regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution obtained in step 7) is injected into the guide plate of the adjustable scraper, the scraper height is adjusted to 5-22 μm, and the casting is performed on a clean glass plate at a speed of 10-50 cm / min. After the casting is completed, the composite film is placed in a closed oven and the oven temperature is maintained at 25-30°C.

[0055] 9) Place the wet film obtained in step 8) in an oven at 25-30°C and dry for 20-30 hours. Move the film in the oven together with the glass plate to a water bath at 0-40°C and soak for 30-60 minutes. Then transfer the film to running tap water and keep it for 12-15 hours. Then transfer the washed film to an electric hot air drying oven and dry it at 15-80°C for 8-12 hours. After drying, a 15-20 μm thick regenerated cellulose / PVDF-HFP / KNN composite film is obtained.

[0056] Step 6: Preparation of a coupled biomass-based nanogenerator with both PENG and TENG

[0057] 10) Cut a circular film with a radius of 1.6 cm from the regenerated cellulose / PVDF-HFP / KNN composite film in step 9), then cut out two copper electrodes with a radius of 1.2 cm, and then cut two wires with a length of 20 cm. Remove 5 cm of the insulating glue outside the two wires to expose the conductive copper wire inside, then spirally coil and bond it to the two copper electrodes, and then bond it to both sides of the circular film in a completely aligned manner. After bonding, a coupled biomass-based nanogenerator with both PENG and TENG is obtained.

[0058] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings:

[0059] Example 1

[0060] A method for preparing a coupled biomass-based nanogenerator having both PENG and TENG, comprising the following steps:

[0061] 1) Preparation of KNN ceramic nanoparticle fillers by solid phase method

[0062] 13.5819g Nb 2 O 5 , 2.1598g Na 2 CO 3 and 4.2583 g K 2 CO 3 Add 40.0g of ball stone and 60.0g of alcohol to the ball mill, mix them thoroughly, and then place the ball mill on a ball mill for 12 hours. Then put the mixture obtained after ball milling into an oven to dry and evaporate the alcohol. Then put the obtained mixture into a grinding mortar and grind it. 2 O 5 、Na 2 CO 3 and K 2 CO 3The mixed powder is crushed and separated from the ball mill with a sieve. The mixed powder obtained after separation is poured into a crucible, and the crucible is covered with a lid and placed in a muffle furnace for firing. The temperature of the muffle furnace is set to 910°C, the heating rate is 3°C / min, and the insulation time is 4h. After that, the fired powder is taken out and poured into a grinding body for grinding for 30min to make the powder fully dispersed, and finally KNN ceramic nanoparticle filler is obtained.

[0063] 2) Preparation of regenerated cellulose solution

[0064] 4 g of cotton linters were crushed with a blender and put into a flask, and 220 g of DMAC solution was added into the flask and the cotton linters were soaked in the DMAC solution for 48 h. After the soaking, the flask was moved to an oil bath-magnetic stirrer and stirred at 160° C. for 30 min to activate cellulose and enhance the bending vibration and stretching vibration of the groups on the cellulose macromolecular chain. When the temperature in the flask dropped to 85° C., the cotton linters were taken out, and the soaked cotton linters were moved to a culture dish to squeeze out a large amount of DMAC solution, and then transferred to a vacuum environment at 50° C. for drying, and the remaining DMAC solution was removed to obtain cotton linters cellulose.

[0065] The obtained 4 g of cotton linter cellulose was added to 60 g of DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution was 1:11; the mixture was stirred at 100° C. for 3 h and then at room temperature for 24 h to obtain a regenerated cellulose casting precursor solution; the flask was then allowed to stand to precipitate impurities in the regenerated cellulose solution.

[0066] Pour the regenerated cellulose solution that has been standing for 48 hours into a centrifuge tube and centrifuge it at a centrifugal speed of 5000r / min for 15 minutes to fully separate the impurities from the regenerated cellulose solution. After the centrifugation, pour the clear and transparent regenerated cellulose solution without impurities in the centrifuge tube into a clean container and seal it for storage.

[0067] 3) Preparation of PVDF-HFP casting precursor solution

[0068] 5 g of PVDF-HFP powder was added to a DMAC / LiCl mixed solution consisting of 1 g of LiCl and 15 g of DMAC solution, and stirred at 40° C. for 1.5 h to obtain a PVDF-HFP casting precursor solution;

[0069] 4) Preparation of regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution

[0070] The PVDF-HFP casting precursor solution and the regenerated cellulose solution were mixed at a mass ratio of 1:10, ultrasonicated for 2 hours, and then heated and stirred at 100℃ for 2 hours. During the ultrasonic stirring process, PVDF-HFP chemically modified the intrachain hydrogen bonds of cellulose, in which the -F chemical bonds with strong electronegativity replaced some hydrogen bonds, enhancing the electronegativity of cellulose, so that a single-electrode mode triboelectric nanogenerator was formed between different electronegative friction materials, and a nano-rough structure was formed in cellulose that was beneficial to enhancing the triboelectric output capacity. After the chemical modification was completed, a regenerated cellulose / PVDF-HFP binary mixed casting precursor solution was obtained; then 1wt.% of KNN ceramic nanoparticle filler accounting for the total mass was added, ultrasonicated for 30 minutes after mixing, and then stirred at room temperature for 30 minutes, and this cycle was repeated 10 times, and finally transferred to a magnetic stirrer and continued to stir for 12 hours, and then ultrasonicated for 1 hour at room temperature, and stirred at 70℃ for 30 minutes to obtain a regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution.

[0071] 5) Preparation of regenerated cellulose / PVDF-HFP / KNN composite film

[0072] The obtained regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution was injected into the guide plate of the adjustable scraper, the scraper height was adjusted to 15 μm, and the casting was carried out on a clean glass plate at a speed of 15 cm / min. After completion, it was placed in a closed oven and the oven temperature was maintained at 30°C.

[0073] The obtained wet film was placed in an oven at 30°C and dried for 24 hours. The film in the oven and the glass plate were moved to a water bath at 5°C and soaked for 60 minutes. The film was then transferred to running tap water and kept for 12 hours. The rinsed film was then transferred to an electric hot air drying oven and dried at 30°C for 12 hours. After drying, a 15 μm thick regenerated cellulose / PVDF-HFP / KNN composite film was obtained.

[0074] 6) Preparation of coupled biomass-based nanogenerators with both PENG and TENG

[0075] A circular film with a radius of 1.6 cm was cut from the dried regenerated cellulose / PVDF-HFP / KNN composite film, and then two copper electrodes with a radius of 1.2 cm were cut, and then two wires with a length of 20 cm were cut. The insulating glue outside the two wires was removed by 5 cm, and the conductive copper wire inside was exposed, and then spirally coiled and bonded to the two copper electrodes, and then bonded to both sides of the circular composite film in a completely aligned manner. After bonding, a coupled biomass-based nanogenerator with both PENG and TENG was obtained.

[0076] Comparative Example

[0077] A method for preparing a regenerated cellulose / KNN composite film, comprising:

[0078] 1) Preparation of KNN ceramic nanoparticle fillers by solid phase method

[0079] The preparation steps of the regenerated cellulose / PVDF-HFP / KNN composite film are the same as those in Example 1;

[0080] 2) Preparation of regenerated cellulose solution

[0081] The preparation steps of the regenerated cellulose / PVDF-HFP / KNN composite film are the same as those in Example 1;

[0082] 3) Preparation of regenerated cellulose / KNN casting precursor solution

[0083] 1 wt.% of KNN ceramic nanoparticle filler was added to the regenerated cellulose solution, and after mixing, ultrasonic treatment was performed for 30 minutes, and then stirring was performed for 30 minutes, and this cycle was repeated 10 times. Finally, the solution was transferred to a magnetic stirrer and stirred for 12 hours. After ultrasonic treatment was performed at room temperature for 1 hour, the solution was stirred at 70°C for 30 minutes to obtain a regenerated cellulose / KNN casting precursor solution.

[0084] 4) Preparation of regenerated cellulose / KNN composite films

[0085] The obtained regenerated cellulose / KNN casting precursor solution was injected into the guide plate of the adjustable scraper, the scraper height was adjusted to 15 μm, and the casting was carried out on a clean glass plate at a speed of 15 cm / min. After completion, it was placed in a closed oven and the oven temperature was maintained at 30°C.

[0086] The obtained wet film was placed in an oven at 30°C and dried for 24 hours. The film in the oven and the glass plate were moved to a water bath at 5°C and soaked for 60 minutes. The film was then transferred to running tap water and kept for 12 hours. The washed film was then transferred to an electric hot air drying oven and dried at 30°C for 12 hours. After drying, a regenerated cellulose / KNN composite film was obtained.

[0087] Figure 1The composition and morphology test diagrams of various materials prepared in Example 1 of the present invention; wherein, (a) is the XRD diagram of KNN ceramic nanoparticle filler, and it can be seen that pure phase KNN ceramic nanoparticle filler without unnecessary miscellaneous substances is prepared by solid phase method; (b) is the XRD diagram of regenerated cellulose / PVDF-HFP / KNN composite film, and it can be seen that the material prepared in Example 1 has no other crystalline phase characteristic peaks except the characteristic peaks of regenerated cellulose, PVDF-HFP and KNN, indicating that the regenerated cellulose / PVDF-HFP / KNN composite film has It has high purity characteristics, and the amorphous peak of 5~35° is the characteristic of regenerated cellulose / PVDF-HFP composite film; (c) is the SEM image of regenerated cellulose / KNN composite film; (d) is the SEM image of regenerated cellulose / PVDF-HFP / KNN composite film; it can be seen that the surface of regenerated cellulose / PVDF-HFP / KNN composite film is obviously rougher than that of regenerated cellulose / KNN composite film, which proves that the addition of PVDF-HFP significantly improves the roughness of cellulose surface, thereby enhancing the triboelectric output capacity of nanogenerator.

[0088] Figure 2 The total current output and the decomposition diagram of the PENG and TENG current output waveforms of the coupled biomass-based nanogenerator with both PENG and TENG prepared in Example 1 of the present invention are measured at different frequencies and different forces; wherein, (a1) is the total current output waveform measured at different frequencies; (a2) is the enlarged view of the total current output waveform measured at different frequencies; (a3) ​​is the decomposition diagram of the PENG part waveform of the total current output at different frequencies; (a4) is the decomposition diagram of the TENG part waveform of the total current output at different frequencies; (b1) is the total current output waveform measured at different forces; (b2) is the enlarged view of the total current output waveform measured at different forces; (b3) is the decomposition diagram of the PENG part waveform of the total current output under different forces; (b4) is the decomposition diagram of the TENG part waveform of the total current output under different forces; it can be seen that the prepared coupled biomass-based nanogenerator with both PENG and TENG meets the synergistic coupling effect of PENG and TENG, thereby enhancing the electrical output capacity of PENG.

[0089] Figure 3The electrical performance test diagram of the coupled biomass-based nanogenerator with both PENG and TENG prepared in Example 1 of the present invention; wherein, (a) is a long-term current output display diagram; (b) is a long-term voltage output display diagram; it can be seen that the prepared coupled biomass-based nanogenerator with both PENG and TENG can maintain a certain electrical output capacity under long-term application conditions, demonstrating the stability of its performance; (c) is a test result diagram of lighting an LED lamp, from which it can be seen that the prepared coupled biomass-based nanogenerator with both PENG and TENG can be well applied in daily life.

[0090] Example 2

[0091] A method for preparing a coupled biomass-based nanogenerator having both PENG and TENG, comprising the following steps:

[0092] 1) Preparation of KNN ceramic nanoparticle fillers by solid phase method

[0093] 13.5819g Nb 2 O 5 , 2.1598 g Na 2 CO 3 and 4.2583 g K 2 CO 3 Add 40.0g of ball stone and 60.0g of alcohol to the ball mill, mix them thoroughly, and then place the ball mill on a ball mill for 12 hours. Then put the mixture obtained after ball milling into an oven to dry and evaporate the alcohol. Then put the obtained mixture into a grinding mortar and grind it. 2 O 5 、Na 2 CO 3 and K 2 CO 3 The mixed powder is crushed and separated from the ball mill with a sieve. The mixed powder obtained after separation is poured into a crucible, and the crucible is covered with a lid and placed in a muffle furnace for firing. The temperature of the muffle furnace is set to 850°C, the heating rate is 3°C / min, and the insulation time is 4h. After that, the fired powder is taken out and poured into a grinding body for grinding for 30min to make the powder fully dispersed, and finally KNN ceramic nanoparticle filler is obtained.

[0094] 2) Preparation of regenerated cellulose solution

[0095] 4 g of cotton linters were crushed with a blender and put into a flask, and 220 g of DMAC solution was added into the flask and the cotton linters were soaked in the DMAC solution for 60 h. After the soaking, the flask was moved to an oil bath-magnetic stirrer and stirred at 160° C. for 30 min to activate cellulose and enhance the bending vibration and stretching vibration of the groups on the cellulose macromolecular chain. When the temperature in the flask dropped to 85° C., the cotton linters were taken out, and the soaked cotton linters were moved into a culture dish to squeeze out a large amount of DMAC solution, and then transferred to a vacuum environment at 50° C. for drying, and the remaining DMAC solution was removed to obtain cotton linters cellulose.

[0096] The obtained 4 g of cotton linter cellulose was added to 60 g of DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution was 1:11; the mixture was stirred at 80° C. for 2 h and then at room temperature for 24 h to obtain a regenerated cellulose casting precursor solution; the flask was then allowed to stand to precipitate impurities in the regenerated cellulose solution.

[0097] Pour the regenerated cellulose solution that has been standing for 48 hours into a centrifuge tube and centrifuge it at a centrifugal speed of 5000r / min for 15 minutes to fully separate the impurities from the regenerated cellulose solution. After the centrifugation, pour the clear and transparent regenerated cellulose solution without impurities in the centrifuge tube into a clean container and seal it for storage.

[0098] 3) Preparation of PVDF-HFP casting precursor solution

[0099] 5 g of PVDF-HFP powder was added to a DMAC / LiCl mixed solution consisting of 1 g of LiCl and 15 g of DMAC solution, and stirred at 40° C. for 1.5 h to obtain a PVDF-HFP casting precursor solution;

[0100] 4) Preparation of regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution

[0101] The PVDF-HFP casting precursor solution and the regenerated cellulose solution were mixed at a mass ratio of 1:20, ultrasonicated for 1 hour, and then heated and stirred at 100℃ for 1 hour. During the ultrasonic stirring process, PVDF-HFP chemically modified the hydrogen bonds in the cellulose chain, in which the -F chemical bonds with strong electronegativity replaced some hydrogen bonds, enhancing the electronegativity of cellulose, so that a single-electrode mode triboelectric nanogenerator was formed between different electronegative friction materials, and a nano-rough structure was formed in cellulose that was beneficial to enhancing the triboelectric output capacity. After the chemical modification was completed, a regenerated cellulose / PVDF-HFP binary mixed casting precursor solution was obtained; then 1wt.% of the total mass of KNN ceramic nanoparticle filler was added, ultrasonicated for 30 minutes after mixing, and then stirred at room temperature for 30 minutes, and this cycle was repeated 10 times, and finally transferred to a magnetic stirrer and continued to stir for 12 hours, and then ultrasonicated at room temperature for 1 hour, and then stirred at 50℃ for 30 minutes to obtain a regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution.

[0102] 5) Preparation of regenerated cellulose / PVDF-HFP / KNN composite film

[0103] The obtained regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution was injected into the guide plate of the adjustable scraper, the scraper height was adjusted to 5 μm, and the casting was carried out on a clean glass plate at a speed of 10 cm / min. After completion, it was placed in a closed oven and the oven temperature was maintained at 25°C.

[0104] The obtained wet film was placed in an oven at 25°C and dried for 30 hours. The film in the oven and the glass plate were moved to a water bath at 5°C and soaked for 60 minutes. The film was then transferred to running tap water and kept for 12 hours. The washed film was then transferred to an electric hot air drying oven and dried at 30°C for 12 hours. After drying, a 15 μm thick regenerated cellulose / PVDF-HFP / KNN composite film was obtained.

[0105] 6) Preparation of coupled biomass-based nanogenerators with both PENG and TENG

[0106] A circular film with a radius of 1.6 cm was cut from the dried regenerated cellulose / PVDF-HFP / KNN composite film, and then two copper electrodes with a radius of 1.2 cm were cut, and then two wires with a length of 20 cm were cut. The insulating glue outside the two wires was removed by 5 cm, and the conductive copper wire inside was exposed, and then spirally coiled and bonded to the two copper electrodes, and then bonded to both sides of the circular composite film in a completely aligned manner. After bonding, a coupled biomass-based nanogenerator with both PENG and TENG was obtained.

[0107] Example 3

[0108] A method for preparing a coupled biomass-based nanogenerator having both PENG and TENG, comprising the following steps:

[0109] 1) Preparation of KNN ceramic nanoparticle fillers by solid phase method

[0110] 13.5819g Nb 2 O 5 , 2.1598g Na 2 CO 3 and 4.2583 g K 2 CO 3 Add 40.0g of ball stone and 60.0g of alcohol to the ball mill, mix them thoroughly, and then place the ball mill on a ball mill for 12 hours. Then put the mixture obtained after ball milling into an oven to dry and evaporate the alcohol. Then put the obtained mixture into a grinding mortar and grind it. 2 O 5 、Na 2 CO 3 and K 2 CO 3 The mixed powder is crushed and separated from the ball mill with a sieve. The mixed powder obtained after separation is poured into a crucible, and the crucible is covered with a lid and placed in a muffle furnace for firing. The temperature of the muffle furnace is set to 950°C, the heating rate is 3°C / min, and the insulation time is 4h. After that, the fired powder is taken out and poured into a grinding body for grinding for 30min to make the powder fully dispersed, and finally KNN ceramic nanoparticle filler is obtained.

[0111] 2) Preparation of regenerated cellulose solution

[0112] 3 g of cotton linters were crushed with a blender and put into a flask, and 220 g of DMAC solution was added into the flask and the cotton linters were soaked in the DMAC solution for 48 h. After soaking, the flask was moved to an oil bath-magnetic stirrer and stirred at 200° C. for 50 min to activate cellulose and enhance the bending vibration and stretching vibration of the groups on the cellulose macromolecular chain. When the temperature in the flask dropped to 90° C., the cotton linters were taken out, and the soaked cotton linters were moved into a culture dish to squeeze out a large amount of DMAC solution, and then transferred to a vacuum environment at 100° C. to dry and remove the remaining DMAC solution to obtain cotton linters cellulose.

[0113] The obtained 3 g of cotton linter cellulose was added to 55 g of DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution was 1:9; the mixture was stirred at 120° C. for 5 h and then at room temperature for 24 h to obtain a regenerated cellulose casting precursor solution; the flask was then allowed to stand to precipitate impurities in the regenerated cellulose solution.

[0114] Pour the regenerated cellulose solution that has been standing for 60 hours into a centrifuge tube and centrifuge it at a centrifugal speed of 5000r / min for 15 minutes to fully separate the impurities from the regenerated cellulose solution. After the centrifugation, pour the clear and transparent regenerated cellulose solution without impurities in the centrifuge tube into a clean container and seal it for storage.

[0115] 3) Preparation of PVDF-HFP casting precursor solution

[0116] 3 g of PVDF-HFP powder was added to a DMAC / LiCl mixed solution consisting of 1 g of LiCl and 10 g of DMAC solution, and stirred at 30°C for 1 h to obtain a PVDF-HFP casting precursor solution;

[0117] 4) Preparation of regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution

[0118] The PVDF-HFP casting precursor solution and the regenerated cellulose solution were mixed in a mass ratio of 1:1, ultrasonicated for 3 hours, and then heated and stirred at 100℃ for 3 hours. During the ultrasonic stirring process, PVDF-HFP chemically modified the intrachain hydrogen bonds of cellulose, in which the -F chemical bonds with strong electronegativity replaced some hydrogen bonds, enhancing the electronegativity of cellulose, so that a single-electrode mode triboelectric nanogenerator was formed between different electronegative friction materials, and a nano-rough structure was formed in cellulose that was beneficial to enhancing the triboelectric output capacity. After the chemical modification was completed, a regenerated cellulose / PVDF-HFP binary mixed casting precursor solution was obtained; then 1wt.% of KNN ceramic nanoparticle filler accounting for the total mass was added, ultrasonicated for 30 minutes after mixing, and then stirred at room temperature for 30 minutes, and this cycle was repeated 5 times, and finally transferred to a magnetic stirrer and continued to stir for 10 hours, and then ultrasonicated at room temperature for 1 hour, and then stirred at 70℃ for 30 minutes to obtain a regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution.

[0119] 5) Preparation of regenerated cellulose / PVDF-HFP / KNN composite film

[0120] The obtained regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution was injected into the guide plate of the adjustable scraper, the scraper height was adjusted to 22 μm, and the casting was carried out on a clean glass plate at a speed of 50 cm / min. After completion, it was placed in a closed oven and the oven temperature was maintained at 30°C.

[0121] The obtained wet film was placed in an oven at 30°C and dried for 24 hours. The film in the oven and the glass plate were moved to a water bath at 5°C and soaked for 60 minutes. The film was then transferred to running tap water and kept for 12 hours. The rinsed film was then transferred to an electric hot air drying oven and dried at 80°C for 8 hours. After drying, a 17 μm thick regenerated cellulose / PVDF-HFP-KNN composite film was obtained.

[0122] 6) Preparation of coupled biomass-based nanogenerators with both PENG and TENG

[0123] A circular film with a radius of 1.6 cm was cut from the dried regenerated cellulose / PVDF-HFP / KNN composite film, and then two copper electrodes with a radius of 1.2 cm were cut, and then two wires with a length of 20 cm were cut. The insulating glue outside the two wires was removed by 5 cm, and the conductive copper wire inside was exposed, and then spirally coiled and bonded to the two copper electrodes, and then bonded to both sides of the circular composite film in a completely aligned manner. After bonding, a coupled biomass-based nanogenerator with both PENG and TENG was obtained.

[0124] Example 4

[0125] A method for preparing a coupled biomass-based nanogenerator having both PENG and TENG, comprising the following steps:

[0126] 1) Preparation of KNN ceramic nanoparticle fillers by solid phase method

[0127] 13.5819g Nb 2 O 5 , 2.1598g Na 2 CO 3 and 4.2583 g K 2 CO 3 Add 40.0g of ball stone and 60.0g of alcohol to the ball mill, mix them thoroughly, and then place the ball mill on a ball mill for 12 hours. Then put the mixture obtained after ball milling into an oven to dry and evaporate the alcohol. Then put the obtained mixture into a grinding mortar and grind it. 2 O 5 、Na 2 CO 3 and K 2 CO3 The mixed powder is crushed and separated from the ball mill with a sieve. The mixed powder obtained after separation is poured into a crucible, and the crucible is covered with a lid and placed in a muffle furnace for firing. The temperature of the muffle furnace is set to 910°C, the heating rate is 3°C / min, and the insulation time is 4h. After that, the fired powder is taken out and poured into a grinding body for grinding for 30min to make the powder fully dispersed, and finally KNN ceramic nanoparticle filler is obtained.

[0128] 2) Preparation of regenerated cellulose solution

[0129] 3 g of cotton linters were crushed with a blender and put into a flask. At the same time, 220 g of DMAC solution was added into the flask and the cotton linters were soaked in the DMAC solution for 72 h. After the soaking, the flask was moved to an oil bath-magnetic stirrer and stirred at 200 ° C for 50 min to activate cellulose and enhance the bending vibration and stretching vibration of the groups on the cellulose macromolecular chain. When the temperature in the flask dropped to 90 ° C, the cotton linters were taken out, and the soaked cotton linters were moved to a culture dish to squeeze out a large amount of DMAC solution, and then transferred to a vacuum environment at 100 ° C for drying, and the remaining DMAC solution was removed to obtain cotton linters cellulose.

[0130] The obtained 3 g of cotton linter cellulose was added to 55 g of DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution was 1:9; the mixture was stirred at 100° C. for 3 h and then at room temperature for 20 h to obtain a regenerated cellulose casting precursor solution; the flask was then allowed to stand to precipitate impurities in the regenerated cellulose solution.

[0131] Pour the regenerated cellulose solution that has been standing for 60 hours into a centrifuge tube and centrifuge it at a centrifugal speed of 5000r / min for 15 minutes to fully separate the impurities from the regenerated cellulose solution. After the centrifugation, pour the clear and transparent regenerated cellulose solution without impurities in the centrifuge tube into a clean container and seal it for storage.

[0132] 3) Preparation of PVDF-HFP casting precursor solution

[0133] 3 g of PVDF-HFP powder was added to a DMAC / LiCl mixed solution consisting of 1 g of LiCl and 10 g of DMAC solution, and stirred at 30°C for 1 h to obtain a PVDF-HFP casting precursor solution;

[0134] 4) Preparation of regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution

[0135] The PVDF-HFP casting precursor solution and the regenerated cellulose solution were mixed at a mass ratio of 1:10, ultrasonicated for 2 hours, and then heated and stirred at 50℃ for 2 hours. During the ultrasonic stirring process, PVDF-HFP chemically modified the intrachain hydrogen bonds of cellulose, in which the -F chemical bonds with strong electronegativity replaced some hydrogen bonds, enhancing the electronegativity of cellulose, so that a single-electrode mode triboelectric nanogenerator was formed between different electronegative friction materials, and a nano-rough structure was formed in cellulose that was beneficial to enhancing the triboelectric output capacity. After the chemical modification was completed, a regenerated cellulose / PVDF-HFP binary mixed casting precursor solution was obtained; then 1wt.% of the total mass of KNN ceramic nanoparticle filler was added, ultrasonicated for 30 minutes after mixing, and then stirred at room temperature for 30 minutes, and this cycle was repeated 5 times, and finally transferred to a magnetic stirrer and continued to stir for 10 hours, and then ultrasonicated at room temperature for 1 hour, and then stirred at 60℃ for 30 minutes to obtain a regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution.

[0136] 5) Preparation of regenerated cellulose / PVDF-HFP / KNN composite film

[0137] The obtained regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution was injected into the guide plate of the adjustable scraper, the scraper height was adjusted to 15 μm, and the casting was carried out on a clean glass plate at a speed of 15 cm / min. After completion, it was placed in a closed oven and the oven temperature was maintained at 27°C.

[0138] The obtained wet film was placed in an oven at 27°C and dried for 20 hours. The film in the oven and the glass plate were moved to a water bath at 5°C and soaked for 60 minutes. The film was then transferred to running tap water and kept for 12 hours. The washed film was then transferred to an electric hot air drying oven and dried at 80°C for 8 hours. After drying, a 17 μm thick regenerated cellulose / PVDF-HFP / KNN composite film was obtained.

[0139] 6) Preparation of coupled biomass-based nanogenerators with both PENG and TENG

[0140] A circular film with a radius of 1.6 cm was cut from the dried regenerated cellulose / PVDF-HFP / KNN composite film, and then two copper electrodes with a radius of 1.2 cm were cut, and then two wires with a length of 20 cm were cut. The insulating glue outside the two wires was removed by 5 cm, and the conductive copper wire inside was exposed, and then spirally coiled and bonded to the two copper electrodes, and then bonded to both sides of the circular composite film in a completely aligned manner. After bonding, a coupled biomass-based nanogenerator with both PENG and TENG was obtained.

[0141] Example 5

[0142] A method for preparing a coupled biomass-based nanogenerator having both PENG and TENG, comprising the following steps:

[0143] 1) Preparation of KNN ceramic nanoparticle fillers by solid phase method

[0144] 13.5819g Nb 2 O 5 , 2.1598 g Na 2 CO 3 and 4.2583 g K 2 CO 3 Add 40.0g of ball stone and 60.0g of alcohol to the ball mill, mix them thoroughly, and then place the ball mill on a ball mill for 12 hours. Then put the mixture obtained after ball milling into an oven to dry and evaporate the alcohol. Then put the obtained mixture into a grinding mortar and grind it. 2 O 5 、Na 2 CO 3 and K 2 CO 3 The mixed powder is crushed and separated from the ball mill with a sieve. The mixed powder obtained after separation is poured into a crucible, and the crucible is covered with a lid and placed in a muffle furnace for firing. The temperature of the muffle furnace is set to 850°C, the heating rate is 3°C / min, and the insulation time is 4h. After that, the fired powder is taken out and poured into a grinding body for grinding for 30min to make the powder fully dispersed, and finally KNN ceramic nanoparticle filler is obtained.

[0145] 2) Preparation of regenerated cellulose solution

[0146] 2 g of cotton linters were crushed with a blender and put into a flask. At the same time, 200 g of DMAC solution was added into the flask and the cotton linters were soaked in the DMAC solution for 60 h. After the soaking, the flask was moved to an oil bath-magnetic stirrer and stirred at 140° C. for 10 min to activate cellulose and enhance the bending vibration and stretching vibration of the groups on the cellulose macromolecular chain. When the temperature in the flask dropped to 80° C., the cotton linters were taken out, and the soaked cotton linters were moved to a culture dish to squeeze out a large amount of DMAC solution, and then transferred to a vacuum environment at 70° C. for drying, and the remaining DMAC solution was removed to obtain cotton linters cellulose.

[0147] The obtained 2 g of cotton linter cellulose was added to 50 g of DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution was 1:12; the mixture was stirred at 100° C. for 3 h and then at room temperature for 30 h to obtain a regenerated cellulose casting precursor solution; the flask was then allowed to stand to precipitate impurities in the regenerated cellulose solution.

[0148] Pour the regenerated cellulose solution that has been standing for 72 hours into a centrifuge tube and centrifuge it at a centrifugal speed of 5000r / min for 15 minutes to fully separate the impurities from the regenerated cellulose solution. After the centrifugation, pour the clear and transparent regenerated cellulose solution without impurities in the centrifuge tube into a clean container and seal it for storage.

[0149] 3) Preparation of PVDF-HFP casting precursor solution

[0150] 2 g of PVDF-HFP powder was added to a DMAC / LiCl mixed solution consisting of 1 g of LiCl and 7 g of DMAC solution, and stirred at 50° C. for 2 h to obtain a PVDF-HFP casting precursor solution;

[0151] 4) Preparation of regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution

[0152] The PVDF-HFP casting precursor solution and the regenerated cellulose solution were mixed at a mass ratio of 1:20, ultrasonicated for 2 hours, and then heated and stirred at 70℃ for 2 hours. During the ultrasonic stirring process, PVDF-HFP chemically modified the intrachain hydrogen bonds of cellulose, in which the -F chemical bonds with strong electronegativity replaced some hydrogen bonds, enhancing the electronegativity of cellulose, so that a single-electrode mode triboelectric nanogenerator was formed between different electronegative friction materials, and a nano-rough structure was formed in cellulose that was beneficial to enhancing the triboelectric output capacity. After the chemical modification was completed, a regenerated cellulose / PVDF-HFP binary mixed casting precursor solution was obtained; then 1wt.% of the total mass of KNN ceramic nanoparticle filler was added, ultrasonicated for 30 minutes after mixing, and then stirred at room temperature for 30 minutes, and this cycle was repeated 7 times, and finally transferred to a magnetic stirrer and continued to stir for 11 hours, and then ultrasonicated at room temperature for 1 hour, and then stirred at 60℃ for 25 minutes to obtain a regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution.

[0153] 5) Preparation of regenerated cellulose / PVDF-HFP / KNN composite film

[0154] The obtained regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution was injected into the guide plate of the adjustable scraper, the scraper height was adjusted to 15 μm, and the casting was carried out on a clean glass plate at a speed of 15 cm / min. After completion, it was placed in a closed oven and the oven temperature was maintained at 30°C.

[0155] The obtained wet film was placed in an oven at 30°C and dried for 24 hours. The film in the oven and the glass plate were moved to a water bath at 0°C and soaked for 30 minutes. The film was then transferred to running tap water and kept for 15 hours. The washed film was then transferred to an electric hot air drying oven and dried at 15°C for 10 hours. After drying, a 20 μm thick regenerated cellulose / PVDF-HFP / KNN composite film was obtained.

[0156] 6) Preparation of coupled biomass-based nanogenerators with both PENG and TENG

[0157] A circular film with a radius of 1.6 cm was cut from the dried regenerated cellulose / PVDF-HFP / KNN composite film, and then two copper electrodes with a radius of 1.2 cm were cut, and then two wires with a length of 20 cm were cut. The insulating glue outside the two wires was removed by 5 cm, and the conductive copper wire inside was exposed, and then spirally coiled and bonded to the two copper electrodes, and then bonded to both sides of the circular composite film in a completely aligned manner. After bonding, a coupled biomass-based nanogenerator with both PENG and TENG was obtained.

[0158] Example 6

[0159] A method for preparing a coupled biomass-based nanogenerator having both PENG and TENG, comprising the following steps:

[0160] 1) Preparation of KNN ceramic nanoparticle fillers by solid phase method

[0161] 13.5819g Nb 2 O 5 , 2.1598 g Na 2 CO 3 and 4.2583 g K 2 CO 3 Add 40.0g of ball stone and 60.0g of alcohol to the ball mill, mix them thoroughly, and then place the ball mill on a ball mill for 12 hours. Then put the mixture obtained after ball milling into an oven to dry and evaporate the alcohol. Then put the obtained mixture into a grinding mortar and grind it. 2 O 5 、Na 2 CO 3 and K 2 CO3 The mixed powder is crushed and separated from the ball mill with a sieve. The mixed powder obtained after separation is poured into a crucible, and the crucible is covered with a lid and placed in a muffle furnace for firing. The temperature of the muffle furnace is set to 950°C, the heating rate is 3°C / min, and the insulation time is 4h. After that, the fired powder is taken out and poured into a grinding body for grinding for 30min to make the powder fully dispersed, and finally KNN ceramic nanoparticle filler is obtained.

[0162] 2) Preparation of regenerated cellulose solution

[0163] 2 g of cotton linters were crushed with a blender and put into a flask, and 40 g of DMAC solution was added into the flask and the cotton linters were soaked in the DMAC solution for 72 h. After the soaking, the flask was moved to an oil bath-magnetic stirrer and stirred at 140° C. for 10 min to activate cellulose and enhance the bending vibration and stretching vibration of the groups on the cellulose macromolecular chain. When the temperature in the flask dropped to 80° C., the cotton linters were taken out, and the soaked cotton linters were moved into a culture dish to squeeze out a large amount of DMAC solution, and then transferred to a vacuum environment at 70° C. for drying, and the remaining DMAC solution was removed to obtain cotton linters cellulose.

[0164] The obtained 2 g of cotton linter cellulose was added to 50 g of DMAC / LiCl mixed solution, wherein the mass ratio of LiCl to DMAC solution in the DMAC / LiCl mixed solution was 1:10; the mixture was stirred at 100° C. for 4 h and then at room temperature for 28 h to obtain a regenerated cellulose casting precursor solution; the flask was then allowed to stand to precipitate impurities in the regenerated cellulose solution.

[0165] Pour the regenerated cellulose solution that has been standing for 72 hours into a centrifuge tube and centrifuge it at a centrifugal speed of 5000r / min for 15 minutes to fully separate the impurities from the regenerated cellulose solution. After the centrifugation, pour the clear and transparent regenerated cellulose solution without impurities in the centrifuge tube into a clean container and seal it for storage.

[0166] 3) Preparation of PVDF-HFP casting precursor solution

[0167] 2 g of PVDF-HFP powder was added to a DMAC / LiCl mixed solution consisting of 1 g of LiCl and 7 g of DMAC solution, and stirred at 50° C. for 2 h to obtain a PVDF-HFP casting precursor solution;

[0168] 4) Preparation of regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution

[0169] The PVDF-HFP casting precursor solution and the regenerated cellulose solution were mixed in a mass ratio of 1:1, ultrasonicated for 1.5 hours, and then heated and stirred at 70℃ for 1.5 hours. During the ultrasonic stirring process, PVDF-HFP chemically modified the intrachain hydrogen bonds of cellulose, in which the -F chemical bonds with strong electronegativity replaced some hydrogen bonds, enhancing the electronegativity of cellulose, so that a single-electrode mode triboelectric nanogenerator was formed between different electronegative friction materials, and a nano-rough structure was formed in cellulose that was beneficial to enhancing the triboelectric output capacity. After the chemical modification was completed, a regenerated cellulose / PVDF-HFP binary mixed casting precursor solution was obtained; then 1wt.% of KNN ceramic nanoparticle filler accounting for the total mass was added, ultrasonicated for 30 minutes after mixing, and then stirred at room temperature for 30 minutes, and this cycle was repeated 7 times, and finally transferred to a magnetic stirrer and continued to stir for 11 hours, and then ultrasonicated at room temperature for 1 hour, and then stirred at 60℃ for 35 minutes to obtain a regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution.

[0170] 5) Preparation of regenerated cellulose / PVDF-HFP / KNN composite film

[0171] The obtained regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution was injected into the guide plate of the adjustable scraper, the scraper height was adjusted to 15 μm, and the casting was carried out on a clean glass plate at a speed of 15 cm / min. After completion, it was placed in a closed oven and the oven temperature was maintained at 30°C.

[0172] The obtained wet film was placed in an oven at 30°C and dried for 24 hours. The film in the oven and the glass plate were moved to a water bath at 40°C and soaked for 40 minutes. The film was then transferred to running tap water and kept for 14 hours. The washed film was then transferred to an electric hot air drying oven and dried at 15°C for 10 hours. After drying, a 20 μm thick regenerated cellulose / PVDF-HFP / KNN composite film was obtained.

[0173] 6) Preparation of coupled biomass-based nanogenerators with both PENG and TENG

[0174] A circular film with a radius of 1.6 cm was cut from the dried regenerated cellulose / PVDF-HFP / KNN composite film, and then two copper electrodes with a radius of 1.2 cm were cut, and then two wires with a length of 20 cm were cut. The insulating glue outside the two wires was removed by 5 cm, and the conductive copper wire inside was exposed, and then spirally coiled and bonded to the two copper electrodes, and then bonded to both sides of the circular composite film in a completely aligned manner. After bonding, a coupled biomass-based nanogenerator with both PENG and TENG was obtained.

[0175] Table 1 Comparison of short-circuit current of the coupled biomass-based nanogenerators with both PENG and TENG prepared in Examples 1-6 and the regenerated cellulose / KNN composite film prepared in the comparative example

[0176]

[0177] Table 1 is a comparison of the short-circuit currents of the coupled biomass-based nanogenerators with both PENG and TENG prepared in Examples 1-6 and the regenerated cellulose / KNN composite film prepared in the comparative example. By controlling the excitation frequency of the exciter and the applied force, the short-circuit currents of the coupled biomass-based nanogenerators with both PENG and TENG prepared in Examples 1-6 and the regenerated cellulose / KNN composite film prepared in the comparative example were tested at a fixed force of 10N and an excitation frequency of 5Hz. It can be seen that the short-circuit current of Example 1 is the largest and the electrical output performance is the best.

[0178] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a coupled biomass-based nanogenerator having both PENG and TENG, characterized in that: The following steps are involved: 1) Mixing a PVDF-HFP casting precursor solution with a regenerated cellulose solution, stirring the solution with ultrasonic for multiple times, and then stirring the solution to obtain a regenerated cellulose / PVDF-HFP binary mixed casting precursor solution; then adding KNN ceramic nanoparticle filler, ultrasonicating the solution again, and heating and stirring the solution to obtain a regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution; casting the regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution, drying the solution once, soaking the solution in a water bath, rinsing the solution, and drying the solution twice to obtain a regenerated cellulose / PVDF-HFP / KNN composite film; 2) The regenerated cellulose / PVDF-HFP / KNN composite film was cut and pasted between two copper electrodes, and the conductive copper wire was spirally coiled and pasted on the two copper electrodes to obtain a coupled biomass-based nanogenerator with both PENG and TENG.

2. The method for preparing a coupled biomass-based nanogenerator having both PENG and TENG according to claim 1, characterized in that: In step 1), the mass ratio of the PVDF-HFP casting precursor solution to the regenerated cellulose solution is 1: (0.1-20); The stirring reaction time is 10 to 12 hours; The mass ratio of the regenerated cellulose / PVDF-HFP binary mixed casting precursor solution to the KNN ceramic nanoparticle filler is 100:1; The heating and stirring is performed at a temperature of 50-70° C. and for a time of 25-35 min.

3. The method for preparing a coupled biomass-based nanogenerator having both PENG and TENG according to claim 1, characterized in that: In step 1), the casting conditions are as follows: injecting the regenerated cellulose / PVDF-HFP / KNN ternary casting precursor solution onto the guide plate of an adjustable scraper, adjusting the scraper height to 5-22 μm, and casting at a speed of 10-50 cm / min; The primary drying temperature is 25-30°C and the time is 20-30h; The conditions for the water bath immersion are: immersion in a water bath at 0-40°C for 30-60 minutes; The flushing conditions are: flushing in running tap water for 12 to 15 hours; The secondary drying condition is 15-80°C for 8-12h; The thickness of the regenerated cellulose / PVDF-HFP / KNN composite film is 15-20 μm.

4. The method for preparing a coupled biomass-based nanogenerator having both PENG and TENG according to claim 1, characterized in that: In step 1), the method for preparing the PVDF-HFP casting precursor solution comprises: adding PVDF-HFP powder and LiCl into a DMAC solution, stirring and reacting, and obtaining the PVDF-HFP casting precursor solution.

5. The method for preparing a coupled biomass-based nanogenerator having both PENG and TENG according to claim 4, characterized in that: The mass ratio of the PVDF-HFP powder, LiCl and DMAC solution is (2-5):1:(7-15); the temperature of the stirring reaction is 30-50°C and the time is 1-2h.

6. The method for preparing a coupled biomass-based nanogenerator having both PENG and TENG according to claim 1, characterized in that: In step 1), the method for preparing the regenerated cellulose solution comprises: soaking the crushed cotton linters in a DMAC solution, heating and stirring the solution once, drying the solution to obtain cotton linters cellulose, adding a DMAC / LiCl mixed solution, heating and stirring the solution twice, standing the solution, and centrifuging the solution to obtain a regenerated cellulose solution.

7. The method for preparing a coupled biomass-based nanogenerator having both PENG and TENG according to claim 6, characterized in that: The mass ratio of the cotton linters to the DMAC solution is 1:(20-100); The temperature of the first heating and stirring reaction is 140-200°C and the time is 10-50 minutes; After the drying, cotton linter cellulose is obtained, wherein the drying temperature is 50-100° C.; The mass ratio of the cotton linter cellulose to the DMAC / LiCl mixed solution is (2-4): (50-60); The DMAC / LiCl mixed solution is prepared by mixing a DMAC solution and LiCl in a mass ratio of 1:(9-12); The conditions for the secondary heating and stirring reaction are: first stirring at 80-120° C. for 2-5 h, then stirring at room temperature for 20-30 h; and the standing time is not less than 48 h.

8. The method for preparing a coupled biomass-based nanogenerator having both PENG and TENG according to claim 1, characterized in that: In step 1), the preparation method of the KNN ceramic nanoparticle filler comprises: fully mixing Nb2O5, Na2CO3, K2CO3, ball stone and alcohol, ball milling, and then drying, grinding, screening, calcining, and grinding again to obtain the KNN ceramic nanoparticle filler; the molar ratio of Nb2O5, Na2CO3 and K2CO3 is 5:2:3; the Nb2O 5、 The mass ratio of the sum of the masses of Na2CO3 and K2CO3: stone: alcohol is 1:2:

3.

9. The method for preparing a coupled biomass-based nanogenerator having both PENG and TENG according to claim 8, characterized in that: The calcination temperature is 850-950° C., the heating rate is 3° C. / min, and the holding time is 4 hours.

10. A coupled biomass-based nanogenerator with both PENG and TENG, characterized in that: It is prepared by the preparation method of the coupled biomass-based nanogenerator having both PENG and TENG as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for simultaneously improving piezoelectric and triboelectric transduction efficiency of composite generator

    CN113708658A

  • Composite nano-generator for intelligent monitoring system and preparation method and application of composite nano-generator

    CN116330773A